Buffalo city metro - is bigger better? The hierarchy of urban labels and why they matter - Nakkungu, Mildred (Department of Environmental and Geographical Science, 2023)
The post-apartheid era in South Africa demonstrated a grand shift in the country's legislation. Local government legislation was particularly affected, as it was at the municipal level that the policies of apartheid were visible. Part of addressing the legacy of spatial segregation included a suite of legislation aimed at addressing the legacy of apartheid and the deep socio-economic inequality present by ensuring that local government had high levels of autonomy. By forging the concept of “developmental local government”, the legislation cemented local government as an active branch of state, able to address the post-apartheid goal of redistribution. My research focuses on one aspect of this legislation, the categorizing of municipalities. South African local government legislation is outlined in a way that provides greater autonomy to municipalities that are deemed “metros” whilst simultaneously describing the model of “cooperative governance” which describes all levels of government as being equally crucial and able to perform governance. The case of Buffalo City Municipality (BCM) forms the focus of my case study because it is an example of a small city that was promoted to ‘metro status'. My research teases out the political and technical hopes, dreams and realities of ‘metro status'. It relies on a narrative qualitative inquiry based on the input from 19 interviewees (including academics, national government ministers and municipal employees) and an analysis of the governmental, legislative and media archives focussed on the local government transformation in the country. Being prompted by the work of Jennifer Robinson, who asks scholars to consider the trajectory of urban labels and the theories they are grounded in, I do not take for granted the jurisdictional/legislative label of “metro” and I seek to answer the question: Is bigger better? Further, the growing questions on the absence of scholarly research on smaller cities gives this research room to ask questions regarding a city caught between larger and smaller cities. BCM demonstrates a municipality whose hopes to be a big city may have been rooted more in appearances rather than in fact. Whilst the term metro speaks to a set of technical assumptions of the characteristics of a city, BCM demonstrates an example of how politics plays a large part in how local government policy is enacted. Where ‘metro status' can be perceived simply as a change in jurisdictional status, BCM demonstrates that even for a small city the prestige of ‘metro status' brings a slew of political and governmental infighting at local, regional and even national level.